Preparation method of high-performance olivine type lithium cobalt phosphate positive electrode material
By adding nano ceria and carbon source to the lithium cobalt phosphate positive electrode material to expand the lithium ion transmission channel, the problems of poor diffusion ability and poor cycle stability are solved, and the cycle stability and low-temperature performance of the battery are significantly improved. It meets the needs of new energy vehicles for long cycle life and changing environments.
Patent Information
- Application Number
- CN202411385033.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
Due to its crystal structure, lithium cobalt phosphate cathode material has poor diffusion ability, poor cycle stability and poor low-temperature performance, which cannot meet the needs of new energy vehicles for long cycle life, large current discharge and variable environments.
Using the cerium doping modification method, the cerium-doped lithium cobalt phosphate positive electrode material is prepared by adding nano cerium dioxide and carbon source to lithium cobalt phosphate, and the cerium-doped lithium cobalt phosphate positive electrode material is expanded, and the lithium ion one-dimensional transmission channel is improved and the material circulation stability is improved. and low temperature performance.
It significantly improves the lithium ion transmission capability, enhances the cycle stability, rate performance and low temperature performance of the battery, and achieves excellent cycle performance at 1 C and high discharge specific capacity at -15°C low temperature.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of olivine-type positive electrode materials for lithium-ion batteries, and in particular to cerium-doped modified lithium cobalt phosphate and a preparation method thereof. Background Art
[0002] In view of global warming and the depletion of fossil fuel resources, the transition to sustainable energy production and storage is a fundamental challenge of this century. Among the new energy storage devices developed, lithium-ion batteries, as one of the chemical power sources, are widely used in digital products, new energy vehicles, national defense and aerospace industries because of their high specific energy density, high operating voltage, long service life and green environmental protection. As countries around the world vigorously develop the new energy vehicle industry, the development of lithium-ion batteries needs to meet the future design requirements for lightweight new energy vehicles. However, the current LiCoO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiMn 2 O 4 and LiFePO 4 The energy density of battery systems such as LiCoO is low, which results in large battery system volume, reduced use cost, maintenance cost and safety. Therefore, in the past few decades, a lot of research work has been devoted to the development of new cathode materials with higher operating voltage, capacity and energy density. In addition, compared with the current mainstream cathode materials such as LiCoO 2 Lower cost and better safety characteristics are also important research directions. 4 The cathode material not only has the safety and reliability of traditional olivine cathode materials, but also has a theoretical specific capacity comparable to that of lithium iron phosphate (167 mAh g −1 ), higher operating voltage (up to 4.8 V) and theoretical energy density (800 Wh kg -1 ). Therefore, in the future, fewer batteries can be used to reduce the complexity of the battery system, improve the safety of the battery system and meet the demand for lightweight batteries for future devices. 4 The research on battery positive electrode materials is of profound significance.
[0003] There are still some problems that hinder the application of lithium cobalt phosphate positive electrode materials, such as poor lithium ion diffusion capacity, poor cycle stability and poor low temperature performance due to its own crystal structure, which cannot meet the needs of long cycle life, high current discharge and variable working environment in practical applications. At present, the modification strategies for the above problems mainly include doping and coating. CN113078307A discloses a method for preparing aluminum phosphate-coated lithium cobalt phosphate positive electrode materials, which realizes the use of fast ion conductor aluminum phosphate to coat the modified lithium cobalt phosphate positive electrode material in one step, avoids the damage of the secondary coating modification to the structure of lithium cobalt phosphate, and can improve the interface stability between the electrode and the electrolyte, thereby improving the cycle stability. CN111533107A discloses a method for preparing a lithium cobalt phosphate-lithium vanadium phosphate composite positive electrode material. The gradient material prepared by this method can better play the advantages of both, and the performance is more superior than the composite material prepared by coprecipitation. The present invention is a new exploration based on the existing research of this research group, and the prepared positive electrode material has ultra-high reversible specific capacity, excellent lithium ion diffusion capacity, high cycle stability and good low temperature performance.
[0004] Therefore, exploring new modification strategies from multiple angles and improving the electrochemical properties of lithium cobalt phosphate cathode materials will help promote the early commercial application of lithium cobalt phosphate cathode materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for modifying lithium cobalt phosphate positive electrode materials with low price, simple method and excellent performance. The specific content mainly includes the following steps: Step S1, the Li source and the P source are lithium hydroxide monohydrate and phosphoric acid respectively, the raw materials are weighed according to the stoichiometric ratio, lithium hydroxide monohydrate is dissolved in deionized water, phosphoric acid is added to diethylene glycol, and then the lithium hydroxide solution is slowly added dropwise to the phosphoric acid solution, and stirred and mixed; Step S2, the Co source is cobalt sulfate heptahydrate, which is weighed and dissolved in ultrapure water according to the stoichiometric ratio, and the above solution is slowly dripped into the S1 mixed solution, and the pH is adjusted to 6.0 with lithium hydroxide aqueous solution. After stirring evenly, it is transferred into the lining of the high-pressure reactor to perform a solvothermal reaction to prepare a precursor slurry; Step S3, washing and centrifuging the obtained precursor with deionized water; Step S4, placing the obtained powder in a vacuum drying oven at 80°C for drying; Step S5, grinding and mixing the dried precursor powder with nano-cerium dioxide and a carbon source in a certain mass ratio; Step S6, placing the uniform mixture in a tube furnace for high-temperature sintering to obtain a cerium-doped lithium cobalt phosphate positive electrode material.
[0006] Furthermore, in step S1, the strong stirring time should be controlled within 55-65 min.
[0007] Furthermore, in step S2, the pH adjuster is a 1M lithium hydroxide aqueous solution, the temperature of the hydrothermal reaction is 200°C, and the reaction time is 12 h.
[0008] Furthermore, in step S4, the drying temperature is controlled to be 80°C.
[0009] Furthermore, in step S5, the amount of nano-cerium dioxide added is controlled to be 2% of the mass of the precursor, and the total mass of the carbon source is controlled to be 15-27wt% of the positive electrode material, preferably 18-22%.
[0010] Further, in step S6, the high temperature sintering process includes a first stage and a second stage of sintering performed sequentially, wherein the temperature of the first stage of sintering is 300°C, and the sintering time of the first stage is 2 hours; the temperature of the second stage of sintering is 650°C, and the sintering time of the second stage is 5 hours, and the sintering atmosphere is Ar / H 2 Mixed gas (95 / 5vol%).
[0011] The advantages of the present invention are embodied in the following aspects: 1. The present invention is characterized by cerium-doped modified lithium cobalt phosphate. The presence of cerium in the carbon layer further increases the content of inorganic matter on the surface of the positive electrode material, which is beneficial to the stability of the interface during the cycle. In addition, cerium is doped into the lithium cobalt phosphate bulk phase, which expands the one-dimensional lithium ion transmission channel, greatly improves the lithium ion transmission capacity, and improves the battery's cycle stability, rate performance and low-temperature performance; 2. Compared with other modification methods, the method of cerium doping to modify lithium cobalt phosphate is relatively simple and can reduce the influence of accidental factors; 3. After the lithium cobalt phosphate positive electrode material prepared by the method described in the present invention is assembled into a lithium ion battery, it has excellent cycle performance at 1 C, good high-rate performance, and still has a high discharge specific capacity at a low temperature of -15°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is the SEM morphology of the modified lithium cobalt phosphate positive electrode material prepared in Example 2.
[0013] Figure 2 This is the SEM morphology of the lithium cobalt phosphate positive electrode material prepared in Comparative Example 1.
[0014] Figure 3 This is the XRD diagram of the prepared lithium cobalt phosphate positive electrode material.
[0015] Figure 4This is the first cycle charge and discharge curve of the button half-cell prepared with lithium cobalt phosphate positive electrode material after activation at 0.1 C.
[0016] Figure 5 This is a comparison of the performance of button-type half-cells made of modified lithium cobalt phosphate positive electrode materials at different rates.
[0017] Figure 6 This is the cycle diagram of a button half-cell at 1 C for preparing lithium cobalt phosphate positive electrode material.
[0018] Figure 7 This is the cycle diagram of the button half-cell for preparing lithium cobalt phosphate positive electrode material at -15℃ and 0.05 C. DETAILED DESCRIPTION Example 1
[0019] The Li source, Co source and P source are LiOH·H 2 O. CoSO 4 7H 2 O, H 3 PO 4 (85 vol%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio is V DEG :V H2O =2.3:1. 30 mmol LiOH·H 2 O was placed in a 50 ml beaker, 10 ml ultrapure water was added and stirred for 10 min until it became transparent and colorless. 10 mmol of H 3 PO 4 Place in a 100 ml reactor liner and add 57.5 ml DEG. After stirring and mixing evenly, add LiOH aqueous solution dropwise to H 3 PO 4 White Li 3 PO 4 The emulsion was stirred vigorously for 1 h. 200 mg of ascorbic acid was weighed and placed in a 50 ml beaker. 15 ml of ultrapure water was added to prevent the formation of Co 2+ Oxidation occurred, stirring until completely dissolved, followed by the addition of 10 mmol CoSO 4 7H 2 O. After the solution is mixed evenly, the obtained Co salt solution is added dropwise to the Li 3 PO 4 The white emulsion was added and the pH value was adjusted to 6.0 with 1M LiOH aqueous solution. The reactor was placed in a 200°C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each and dried at 80°C to obtain LiCoPO 4 Precursor. Mix the precursor, 1% CeO 2(accounting for the mass fraction of the positive electrode material) and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material) were placed in a mortar and ground for 20 min. The powder was placed in a tube furnace and heated at 95Ar / 5H 2 The modified LiCoPO was obtained by pre-calcining at 300 °C for 2 h under atmosphere, then heating to 650 °C for 5 h and cooling naturally to room temperature. 4 / C-1%Ce positive electrode material. Example 2
[0020] The Li source, Co source and P source are LiOH·H 2 O. CoSO 4 7H 2 O, H 3 PO 4 (85 vol%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio is V DEG :V H2O =2.3:1. 30 mmol LiOH·H 2 O was placed in a 50 ml beaker, 10 ml ultrapure water was added and stirred for 10 min until it became transparent and colorless. 10 mmol of H 3 PO 4 Place in a 100 ml reactor liner and add 57.5 ml DEG. After stirring and mixing evenly, add LiOH aqueous solution dropwise to H 3 PO 4 White Li 3 PO 4 The emulsion was stirred vigorously for 1 h. 200 mg of ascorbic acid was weighed and placed in a 50 ml beaker. 15 ml of ultrapure water was added to prevent the formation of Co 2+ Oxidation occurred, stirring until completely dissolved, followed by the addition of 10 mmol CoSO 4 7H 2 O. After the solution is mixed evenly, the obtained Co salt solution is added dropwise to the Li 3 PO 4 The white emulsion was added and the pH value was adjusted to 6.0 with 1M LiOH aqueous solution. The reactor was placed in a 200°C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each and dried at 80°C to obtain LiCoPO 4 Precursor. Mix the precursor, 2% CeO 2 (accounting for the mass fraction of the positive electrode material) and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material) were placed in a mortar and ground for 20 min. The powder was placed in a tube furnace and heated at 95Ar / 5H 2The modified LiCoPO was obtained by pre-calcining at 300 °C for 2 h under atmosphere, then heating to 650 °C for 5 h and cooling naturally to room temperature. 4 / C-2%Ce positive electrode material. Example 3
[0021] The Li source, Co source and P source are LiOH·H 2 O. CoSO 4 7H 2 O, H 3 PO 4 (85 vol%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio is V DEG :V H2O =2.3:1. 30 mmol LiOH·H 2 O was placed in a 50 ml beaker, 10 ml ultrapure water was added and stirred for 10 min until it became transparent and colorless. 10 mmol of H 3 PO 4 Place in a 100 ml reactor liner and add 57.5 ml DEG. After stirring and mixing evenly, add LiOH aqueous solution dropwise to H 3 PO 4 White Li 3 PO 4 The emulsion was stirred vigorously for 1 h. 200 mg of ascorbic acid was weighed and placed in a 50 ml beaker. 15 ml of ultrapure water was added to prevent the formation of Co 2+ Oxidation occurred, stirring until completely dissolved, followed by the addition of 10 mmol CoSO 4 7H 2 O. After the solution is mixed evenly, the obtained Co salt solution is added dropwise to the Li 3 PO 4 The white emulsion was added and the pH value was adjusted to 6.0 with 1M LiOH aqueous solution. The reactor was placed in a 200°C forced air drying oven for hydrothermal reaction for 12 hours. The hydrothermal product was washed with ultrapure water and ethanol three times each and dried at 80°C to obtain LiCoPO 4 Precursor. Precursor, 5% CeO 2 (accounting for the mass fraction of the positive electrode material) and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material) were placed in a mortar and ground for 20 min. The powder was placed in a tube furnace and heated at 95Ar / 5H 2 The modified LiCoPO was obtained by pre-calcining at 300 °C for 2 h under atmosphere, then heating to 650 °C for 5 h and cooling naturally to room temperature. 4 / C-5%Ce positive electrode material. Comparative Example 1
[0022] The Li source, Co source and P source are LiOH·H 2 O. CoSO 4 7H 2 O, H 3 PO 4 (85 vol%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio is V DEG :V H2O =2.3:1. 30 mmol LiOH·H 2 O was placed in a 50 ml beaker, 10 ml ultrapure water was added and stirred for 10 min until it became transparent and colorless. 10 mmol of H 3 PO 4 Place in a 100 ml reactor liner and add 57.5 ml DEG. After stirring and mixing evenly, add LiOH aqueous solution dropwise to H 3 PO 4 White Li 3 PO 4 The emulsion was stirred vigorously for 1 h. Weigh 200 mg of ascorbic acid into a 50 ml beaker and add 15 ml of ultrapure water to prevent the formation of Co 2+ Oxidation occurred, stirring until completely dissolved, followed by the addition of 10 mmol CoSO 4 7H 2 O. After the solution is mixed evenly, the obtained Co salt solution is added dropwise to the Li 3 PO 4 The white emulsion was added and the pH value was adjusted to 6.0 with 1M LiOH aqueous solution. The reactor was placed in a 200°C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each and dried at 80°C to obtain LiCoPO 4 Precursor. The precursor and 21% mixed carbon source (mass fraction of positive electrode material) were ground in a mortar for 20 min, and the powder was placed in a tube furnace under 95Ar / 5H 2 The modified LiCoPO was obtained by pre-calcining at 300 °C for 2 h under the atmosphere, then heating to 650 °C for 5 h and cooling naturally to room temperature. 4 / C positive electrode material.
[0023] Figure 1 and Figure 2 They are SEM morphology images of the modified lithium cobalt phosphate positive electrode material prepared in Example 2 and the lithium cobalt phosphate positive electrode material prepared in Comparative Example 1. By comparison, it is found that after Ce doping, the grain size is significantly reduced, which helps to shorten the transmission distance of Li+, and at the same time allows the electrolyte to be effectively infiltrated, increasing the contact area.
[0024] Figure 3It is the XRD spectrum of the positive electrode materials prepared by the methods described in Examples 1, 2, 3, and Comparative Example 1, where 2Thate is the diffraction angle and Intensity is the peak intensity. The six groups of positive electrode materials are compared with the standard card JCPDS No.89-6192 and all meet the requirements of olivine-type positive electrode materials, belonging to the Pnmb space group. Four groups of positive electrode materials have strong diffraction peaks, indicating good crystallinity.
[0025] Figure 4 This is the first cycle charge and discharge curve, where Capacity is the discharge specific capacity and Voltage is the voltage. By comparison, it is found that after doping modification, the discharge capacity has been significantly improved, and the 4.75V voltage platform has been significantly extended. At the same time, the polarization between charge and discharge (the difference between the charge voltage and the discharge voltage at the same potential) is reduced, which is conducive to the reversible cycle of the battery.
[0026] Figure 5 , Figure 6 and Figure 7 It is the electrochemical performance test diagram, Cycle number is the number of cycles, and Capacity is the discharge specific capacity. Figure 5 The discharge capacity at different rates was tested. After Ce doping, the rate performance was significantly improved. At the same time, the stability was significantly improved during the 1C cycle at room temperature ( Figure 6 ). Figure 7 This is a cycle diagram of a button half-cell for preparing lithium cobalt phosphate positive electrode material at -15°C and 0.05°C. In Example 2, lithium cobalt phosphate can still release about 100 mAh g -1 This provides important ideas for the practical application of batteries at low temperatures.
[0027] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
[0028] Although the above describes the specific implementation methods of the present invention, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance olivine-type lithium cobalt phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: Step S1, weighing a Li source according to a certain stoichiometric ratio, dissolving it in a certain amount of ultrapure water, and stirring; Step S2, weighing a P source according to a certain stoichiometric ratio, dissolving it in a certain amount of diethylene glycol, and stirring; Step S3, adding the solution obtained in S1 dropwise to the solution in S2, and stirring until uniformly mixed; Step S4, weighing the Co source according to a certain stoichiometric ratio, dissolving it in a certain amount of ultrapure water, and vigorously stirring it. Slowly drop the solution obtained in S2 into the mixed solution in S3, adjust the pH value to 6.0, and perform a solvothermal reaction to prepare a precursor material; Step S5, washing, centrifuging and drying the obtained material; Step S6, grinding the precursor powder obtained in S5 with nano-cerium dioxide and a carbon source in a certain mass ratio; Step S7, placing the evenly ground mixture in a tube furnace for high-temperature sintering to obtain a cerium-doped lithium cobalt phosphate positive electrode material.
2. According to the preparation method of claim 1, the optimal addition ratio of deionized water to diethylene glycol is 1:2~2.5 (volume ratio), preferably 1:2.
3.
3. The preparation method according to claim 1, characterized in that In step S3, after the Li salt solution is added dropwise to the P source solution, the stirring time is 50-90 minutes, preferably 60-70 minutes.
4. The preparation method according to claim 1, characterized in that In step S4, the temperature of the hydrothermal reaction is 160-220° C., and the reaction time is 10-15 h, preferably the reaction temperature is 200° C., and the reaction time is 12 h.
5. The preparation method according to claim 1, characterized in that In step S6, the amount of nano-cerium dioxide added is controlled to be 1% to 5% of the mass of the precursor, preferably 2%, and the total mass of the carbon source is controlled to be 15 to 27 wt% of the positive electrode material, preferably 18-22%.
6. The preparation method according to claim 1, characterized in that In step S7, the high-temperature sintering process includes a first stage and a second stage of sintering performed sequentially, wherein the temperature of the first stage of sintering is 300°C, and the sintering time of the first stage is 2-3 h; the temperature of the second stage of sintering is 650-720°C, and the sintering time of the second stage is 5-9 h, and the sintering atmosphere is Ar / H2 mixed gas (95 / 5 vol%).
Citation Information
Patent Citations
Preparation method of lithium cobalt phosphate-lithium vanadium phosphate composite positive electrode material
CN111533107A
Lithium ion battery positive electrode material composed of cerium oxide and carbon co-coated lithium vanadium phosphate and preparation method thereof
CN103985863A
Rare earth element modified lithium ion battery positive electrode material and preparation method and application thereof
CN110911687A
Preparation method of cerium dioxide modified lithium manganese iron phosphate electrode material
CN115275170A
Modification method of high-voltage olivine-type lithium cobalt phosphate positive electrode material
CN118458721A
